Total Pancreatectomy With Intraportal Islet Autotransplantation as a Treatment of Chronic Pancreatitis in Patients With CFTR Mutations. Issue 2 (February 2018) - Colling, Kristin P.; Bellin, Melena D.; Schwarzenberg, Sarah J.; Berry, Louise; Wilhelm, Joshua J.; Dunn, Ty; Pruett, Timothy L.; Sutherland, David E.R.; Chinnakotla, Srinath; Dunitz, Jordan M.; Beilman, Greg J.
Abstract : Objectives: Chronic pancreatitis (CP) is an infrequent but debilitating complication associated with CFTR mutations. Total pancreatectomy with islet autotransplantation (TPIAT) is a treatment option for CP that provides pain relief and preserves β-cell mass, thereby minimizing the complication of diabetes mellitus. We compared outcomes after TPIAT for CP associated with CFTR mutations to CP without CTFR mutations. Methods: All TPIATs performed between 2002 and 2014 were retrospectively reviewed: identifying 20 CFTR homozygotes (cystic fibrosis [CF] patients), 19 CFTR heterozygotes, and 20 age-/sex-matched controls without CFTR mutations. Analysis of variance and χ 2 tests were used to compare groups. Results: Baseline demographics were not different between groups. Postoperative glycosylated hemoglobin and C-peptide levels were similar between groups, as were islet yield and rate of postoperative complications. At 1 year, 40% of CF patients, 22% of CFTR heterozygotes, and 35% of control patients were insulin independent. Conclusion: Total pancreatectomy with islet autotransplantation is a safe, effective treatment option for CF patients with CP, giving similar outcomes for those with other CP etiologies.